Reversible-hydrogen-transfer-mediated anomerization of azaheterocyclyl 2-deoxy-C-glycosides and mechanistic studies - Mu, Qiu-Qi (2023)
Mutarotation of O-glycans and O-glycosides has long been well-established and exploited in the stereocontrolled chemical synthesis of O-glycosides, while few examples of C-glycoside anomerization are known to date. During the development of a simple iridium catalyst-promoted α-stereoselective C-glycosylation of 2-indoly-pyridine with glycal donors, we serendipitously discovered the occurrence of 2-deoxy-C-glycoside anomerization, enabling α-to-β configuration conversion. Control experiments and density functional theory calculations were performed to explore the mechanistic details of the anomerization of the C-glycosylation products, which could tolerate C-aryl and C-alkyl-glycosides. The anomerization reaction plausibly proceeds through the pathway involving the activation of the C(sp3)-H bond mediated by the iridium catalyst and reversible hydrogen transfer, rather than the classical anomerization mechanisms involving the endocyclic cleavage of the C1-O5 bond or exocyclic cleavage of the glycosidic bond.